PANDANGAN HUKUM ISLAM TERHADAP AKAD BAI’ ISTIGHLẨL - Ar, Jefri; Ramadhan, Taufiq (Universitas Darunnajah Jakarta, Indonesia, 2024)
This study aims to explain the concept of bai' istiglāl, the differences of scholarly opinion regarding its ruling, and the reasons for the differences of opinion. Bai' istiglāl is the sale of goods made in bai' wafa', then the seller leases the goods back. The research method used is a qualitative method with a literature review approach or literature study. The result of the research is that some scholars allow the practice of bai' istiglāl on the grounds that buying and selling is a permissible thing in general, and there is an element of leasing that is permissible. While some other scholars prohibit this practice because it is considered to contain elements of usury and the merging of two prohibited contracts. This difference of opinion occurs due to the absence of a clear text regarding the ruling of bai' istiglāl, as well as the debate over the element of lending and profit-taking in it. After comparing the arguments of the two groups, the author tends to argue that the practice of bai' istiglāl is permissible for several reasons, including because there are no harmful elements and it is more in line with the public good